Implementation of Android-Based Learning Media on Temperature and Heat Materials to Enhance Student Motivation and Learning Outcomes in Senior High Schools - Nova Elysia Ntobuo; Lanto Ningrayati Amali; Lanto Mohamad Kamil Amali; Nancy Katili (Postgraduate, University of Mataram, 2023)
This study aims to enhance the motivation and learning outcomes of high school students at SMA Negeri 7 Gorontalo for the 2022/2023 Academic Year through implementing android-based learning media on temperature and heat materials. The research method is a quasi-experimental design with a one-group pretest-posttest research design. The research sample consisted of 3 classes: class X IPA 2 as the experiment class and class X IPA 3, and X IPA 4 as a replica class. This research begins with preparing learning tools to implement learning media based on Android material on temperature and heat. The results of the validation show that the learning tools are valid and can be used in the learning process. Implementing the learning process in this study is in the very good category. It can increase student motivation and learning outcomes, where the N-Gain scores for the experimental and replica classes are in the high category.